Tradisi Nyabis Sebagai Simbol Ethict of Care Kyai - Rahman, Mufiqur (Proceedings of Annual Conference for Muslim Scholars, 2019)
Nyabis tradition conducted not only caused of pragmatism motivation of public civil societies to succeed their effort but also conducted as the spiritual effort to have been accepted Barokah (blessing from God) this research strengthen tradition it’s self that nyabis is not only the matter of pragmatism but also the fact of ethics of care that has been done by Kyai as the utilitarianism that created cavil’s trust and obedient.